2007
DOI: 10.1111/j.1462-5822.2007.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides from atherosclerosis-associated bacteria antagonize TLR4, induce formation of TLR2/1/CD36 complexes in lipid rafts and trigger TLR2-induced inflammatory responses in human vascular endothelial cells

Abstract: SummaryInfection with bacteria such as Chlamydia pneumonia, Helicobacter pylori or Porphyromonas gingivalis may be triggering the secretion of inflammatory cytokines that leads to atherogenesis. The mechanisms by which the innate immune recognition of these pathogens could lead to atherosclerosis remain unclear. In this study, using human vascular endothelial cells or HEK-293 cells engineered to express pattern-recognition receptors (PRRs), we set out to determine Toll-like receptors (TLRs) and functionally as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(125 citation statements)
references
References 48 publications
7
118
0
Order By: Relevance
“…Therefore, in addition to the invasion deficiency, DPG3 lacks FimA, a known potent TLR2 ligand, and pathogenicity may be reduced to only LPS (36 -38, 40). Our recent investigation corroborated by other laboratories shows that TLR2 Ϫ/Ϫ mice exhibit substantially reduced lesions of P. gingivalis-induced atherosclerosis compared with TLR2 ϩ/ϩ and TLR2 ϩ/Ϫ mice, and mice injected with FSL-1, a TLR2 agonist, also showed a similar increase in atherosclerotic lesion size, irrespective of the diet (4,(42)(43)(44). The reduction of atherosclerosis observed when animals were infected with DPG3 may not be the result of only lack of invasion capability, but also lack of cell surface-initiated signaling by the FimA.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, in addition to the invasion deficiency, DPG3 lacks FimA, a known potent TLR2 ligand, and pathogenicity may be reduced to only LPS (36 -38, 40). Our recent investigation corroborated by other laboratories shows that TLR2 Ϫ/Ϫ mice exhibit substantially reduced lesions of P. gingivalis-induced atherosclerosis compared with TLR2 ϩ/ϩ and TLR2 ϩ/Ϫ mice, and mice injected with FSL-1, a TLR2 agonist, also showed a similar increase in atherosclerotic lesion size, irrespective of the diet (4,(42)(43)(44). The reduction of atherosclerosis observed when animals were infected with DPG3 may not be the result of only lack of invasion capability, but also lack of cell surface-initiated signaling by the FimA.…”
Section: Discussionsupporting
confidence: 75%
“…The study by Triantafilou et al (28) showed that the silencing of TLR7 did not affect the production of TNF-␣ in human vascular endothelial cells in response to P. gingivalis LPS. However, in our study we used macrophages, a cell type that is different from endothelial cells, which can explain the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Another widely studied surface structure of P. gingivalis is its LPS, which displays significant structural and biological differences from the LPS of E. coli (34). Both P. gingivalis and its purified cell surface components (LPS and FimA) are detected predominantly by TLR2 of the innate immune system resulting in host cell activation (9,28,35), although activation of TLR4 by P. gingivalis LPS has also been reported (14). Our previous studies demonstrated that macrophages respond differently to live P. gingivalis, when compared with its LPS or its FimA, in the context of cytokine secretion and intracellular molecule induction (7,9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin & its analog octreotide is the primary drug that is used in preparation. It inhibits the exocrine and endocrine secretions from gut thereby controlling signs and symptoms of Carcinoid tumor and preventing Carcinoid crisis [14,15]. The half-life of somatostatin is 1 to 3 min, and that of octreotide is 1.5 to 3 hrs.…”
Section: Preoperative Preparation Of the Patientmentioning
confidence: 99%